Features of the Formation of Economic Sustainability at Different Stages of the Enterprise’s Functioning - Butnik-Sivers?kyy Oleksandr B. (Problemi Ekonomiki, 2017)
Given the importance of stakeholders in ensuring economic sustainability, the aim of the article is to determine the priority of their groups at different stages of the enterprise’s functioning (creation, adaptation, growth, development). It is shown that at the stage of creating the company, the priority stakeholders are the shareholders and creditors as providers of financial resources, as well as customers as the source of formation of the market resource. At the growth stage, stakeholders should be ranked based on their ability to meet the company’s needs at the new level and create conditions for expanding the debt financing tools. It is noted that the formed high ranking positions of the enterprise reduce the role of financial stakeholders and actualize the priority of partnership relations that ensure its innovative development. Attention is focused on the fact that corporate conflicts: “agent-principal” and “principal-principal” present the threat of loss of economic sustainability at any stage of the enterprise’s functioning, which requires their compromise resolving. It is stated that the formation of the economic sustainability of enterprises is largely determined by the expansion of partnership relations and balancing the interests of stakeholders. The latter should be based on the priority of the resource contribution (volume, specificity of resources) and the opportunities of the influence of a certain interested party on the company (destructive, constructive ones).